Analisi e trasmissione di Messaggi di Allerta per la Gestione delle Emergenze Ambientali - Cefalo, Raffaella; Cramastetter, Sabrina; Maver, Simone; Paparini, Claudia (GEOmedia, 2014)
Environmental Disaster Management requires quick respounce times and an efficient resources use. An efficient answer is necessary, thanks to Alerting messages integrated by accurate georeferenced event informations. The general scheme for rescue situation answer requires phenomenon knowledge, environmental monitoring, rapid Alerting services, quick intervention times and an optimum resources use. Police and emergencies management services need affordable knowledge of Disaster location, in order to efficiently coordinate rescue teams. This is particularly critic when traditional infrastructures are not operational due to the emergency conditions themselves (i.e. floodings, earthquakes, landslides, oils spilling, humanity intervention operations). In this paper a contribution to the prevention and management of environmental disasters, by the analysis of parameters relative to the identification and georeferencing of different tipologies of natural and anthropic disasters, is given. The strutture of CAP (Common Alerting Protocol) version 1.2, implemented by Oasis, USA, giving the Alerting messages structure that can be sent simultaneously to different emergency management systems, simplyfing the operations requested to the teams involved into rescue operations, has been herein analyzed. Alert Messages trasmission Systems have been also analyzed, included the possibility to use EGNOS (European Geostationary Navigation Overlay System) SIS (Signal In Space). The final aim of this research is the extraction and real time visualization of georeferenced informations on a mobile device (PDA, mobile phone).